2000
DOI: 10.1097/00002480-200005000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Equilibrated Urea in Children on Chronic Hemodialysis

Abstract: Urea rebound (UR) after hemodialysis (HD) requires the use of equilibrated urea (Ceq) instead of immediate end-dialysis urea (Ct) for correct quantification of HD, which is impractical. A new formula for predicting Ceq in children is suggested in our study. Thirty eight standard pediatric HD sessions (single pool Kt/V = 1.70 +/- 0.35, K = 4.65 +/- 1.14 ml/min/kg, UF coeff. = 3.2-6.2 ml/h/mm Hg, t = 3.80 +/- 0.46 h) in 15 children (M: 6, F: 9), ages 14.5 +/- 3.28 years were analyzed. Blood samples were taken: b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The measures most widely used to gauge dialyzer treatment are Kt / V , that is dialyzer urea clearance ( K ) multiplied by duration ( t ) of the dialysis session and divided by urea volume ( V ) of distribution, and the normalized protein catabolic rate (nPCR) [57, 58, 59]. Urea dialytic reduction rate (URR) is derived from the pre and post-dialysis serum urea values and quantitates urea removal by dialysis.…”
Section: Guideline 10: Urea Dialytic Kinetic Dialysis Dose and Protmentioning
confidence: 99%
See 1 more Smart Citation
“…The measures most widely used to gauge dialyzer treatment are Kt / V , that is dialyzer urea clearance ( K ) multiplied by duration ( t ) of the dialysis session and divided by urea volume ( V ) of distribution, and the normalized protein catabolic rate (nPCR) [57, 58, 59]. Urea dialytic reduction rate (URR) is derived from the pre and post-dialysis serum urea values and quantitates urea removal by dialysis.…”
Section: Guideline 10: Urea Dialytic Kinetic Dialysis Dose and Protmentioning
confidence: 99%
“…URR is also correlated with the amount of urea dialytic removal ( Kt ) compared to the amount of urea body content ( V ) and thus to Kt / V . Usually urea dialytic clearance in children is low in comparison with the high Kie which is between 200 to 1000 mL min −1 (6 to 12 mL min −1  kg −1 BW) [58, 61]. Nevertheless, after dialysis the concentration of urea in plasma increases rapidly in an initial period, usually until 60 min postdialysis [62].…”
Section: Guideline 10: Urea Dialytic Kinetic Dialysis Dose and Protmentioning
confidence: 99%
“…While there is an advantage in that these methods avoid taking a blood sample after HD and do not detain the patient beyond the treatment time, the accuracy of these methods is influenced by the method and timing of taking the intradialytic blood sample (13,14). If severe vascular access recirculation is present, and if the blood sample is taken at full blood flow without slowing or stopping it to prevent sample dilution with recirculated blood, the intradialytic BUN will be artificially low and will result in significant overestimation of the true eqBUN, and as a consequence a significant underestimation of the true Kt/ V ‐value (15). Thus, it is necessary to pay careful attention to the method of intradialytic blood sample when they were performed.…”
Section: Discussionmentioning
confidence: 99%
“…2,8,9 To take into account the post-HD urea rebound (UR) 10 -12 and quantify the delivered HD dose, such a method requires a blood sample 1 hour after HD to obtain the true equilibrated blood urea nitrogen (BUN) and Kt/V. [13][14][15][16][17] This additional sampling 1 hour after the completion of dialysis can be difficult to obtain in the pediatric setting, making the determination of delivered HD difficult to calculate. There is therefore a need for a simple and accurate determination of HD dose and treatment adjustments in the pediatric population, because size, dynamics of substance handling, and volume of distribution of substances to be cleared in children vary greatly from infancy through adolescence, and ultimately adulthood.…”
Section: The North American Pediatric Renal Trials and Collaborativementioning
confidence: 99%
“…Results of this work were previously published. 12,15,17 For use in the current study, this dataset was de-identified and therefore exempt from Institutional Review Board (IRB) approval.…”
Section: Subjects and Datamentioning
confidence: 99%